Effect of traffic congestion on infrastructure capacity: modeling commuters’ behavior towards “stick & carrot” strategies to better manage infrastructure network: the case study of Cairo - Thabet, M.; Abdelgawad, H.; Osman, H.; El-Said, M. (International Journal of Engineering and Technology, 2019)
In Cairo, alike many mega cities, suffers from the consequences of urban sprawl and traffic congestions. Recent studies report the cost of congestion in the Greater Cairo Area amounting to 4% of the nation’s GDP. Traditionally governments have addressed congestion by boosting infrastructure capacity to meet increased demand. Although in some cases this expansion is inevitable, it has proven unsustainable on the long run. An alternative approach is to manage and control the demand given the existing infrastructure using different strategies. One such strategy aims to influence the behavior of transportation users to manage the demand. This study investigates two distinct - but related - approaches to influence traveler behavior. The “stick & carrot” technique applies both congestion pricing and peak-avoidance rewards to travelers. This paper models the change of commuters’ behavior by measuring and comparing their willingness to pay (WTP) and attitude to earn (ATE) during peak hour travel. A mixed stated preference/revealed preference survey is developed and distributed online to investigate the effect of congestion on commuters’ daily travel behavior. The collected responses are analyzed and modeled using a binary logit model for commuters’ behavioral change for both their WTP and ATE potentials. Results indicate that there is a massive congestion problem in Cairo that people really suffer from, and it affects their daily life decisions, also, they seem not to prefer congestion pricing technique, while they prefer to be rewarded instead. Furthermore, a comprehensive development of Cairo’s public transport network should be implemented. The obtained models from collected data emphasizes the previous hypothesis.
Keywords: Cairo; Capacity Management; Congestion Pricing; Infrastructure Network; Modeling; Peak-Avoidance Rewards; Traffic Congestion.